Application of Guided Endodontics to locate the calcified root canal with periapical lesion: case report (Research, Society and Development, 2021)
A contemporary endodontic solution for the endodontic treatment of calcified root canals is characterized by guided endodontics. The aim of this study was to describe a guided endodontics treatment, which is a technique that facilitates access to root canals with pulp calcifications. Female patient, 40 years old, sought care at the Dental Clinic complaining of: “darkened tooth”. The radiographic examination revealed a highly calcified root canal from unit 21, with the presence of a periapical lesion. Thus, the technique using an endodontic guide was indicated, in order to securely locate the root canal. Once located, the canal was prepared and filled in a conventional manner, within the limitations presented by the excessive formation of dentin in such a unit. Although it is a technique recently introduced in the literature, guided endodontics guarantees a shorter work time, and has been shown to be a safe and precise technique, facilitating access and allowing for a safe, agile and predictable endodontic treatment.